Crack nucleation and growth during dynamic indentation of chemically-strengthened glass. (July 2020) - Kang, M.; Li, W.; Leong, A.F.T.; Guan, M.; Fezzaa, K.; Harris, J.T.; Ramesh, K.T.; Hufnagel, T.C.
Abstract: Dynamic point impact loading is a primary cause of fracture of glass screens on mobile devices. An improved understanding of crack initiation and evolution under high-speed indentation could contribute to the development of materials with better performance, but experimental observations are challenging due to the short timescales and limited depth-of-field of optical microscopy. To address this need, we have observed fracture of a chemically-strengthened glass during dynamic indentation using in situ x-ray phase-contrast imaging (XPCI). Median cracks initiate below the surface of the glass, at a depth approximately corresponding to the depth at which the surface residual compressive stress diminishes to zero. These cracks initially propagate at ∼ 10 m s − 1, rapidly accelerating to > 100 m s − 1 . We also observe some evidence for rate-dependent behavior, in that indentation at the lowest rates studied here (below about ∼ 0 . 15 m s − 1 ) fails to initiate cracks regardless of the depth of the indentation (up to 18 μ m ), while indentation at higher rates produces median cracks that either arrest or cause complete fracture, depending on the depth of indentation.